Fast dissolving meloxicam formulation for acute dental pain: Thoughts to ponder - AJP, Editor (Asian Journal of Pharmaceutics (AJP), 2014)
In the April-June issue of Asian Journal of Pharmaceutics 2008, Inamdar et al. have reported the development of a new formulation of meloxicam based on solid dispersion technique using a number of polymers.[1] This eloquently performed work demonstrated that via the incorporation of optimized solid dispersion attributes into fast disintegrating tablets it is possible to further enhance the dissolution profile of meloxciam such that within 1 min almost 95% of the drug release occurred under ideal conditions of dissolution